Study on the antioxidant and antiosteoporotic activities of the oyster peptides prepared by ultrasound-assisted enzymatic hydrolysis - Zhengze Quan; Zonghan Wang; Zixu Wang; Zuoxu Hou; Bin Liu; Xiaoming Guo; Beiwei Zhu; Yuanyuan Hu (Ultrasonics Sonochemistry)
In this study, the effects of ultrasound-assisted enzymatic hydrolysis on the production of antioxidant and antiosteoporotic peptides derived from oysters were investigated. Results showed that ultrasound-assisted enzymatic hydrolysis significantly enhanced the peptide content, free radical scavenging ability, and ferric reducing antioxidant power of total oyster protein hydrolysate (TOPH), with optimal results achieved at 200 W (TOPH-200). Correspondingly, ultrasound treatment at 200 W increased the exposure of hydrophobic regions, reduced α-helix content, and facilitated the generation of small molecular weight peptides in TOPH. In an H2O2-induced oxidative damage model of osteoblastic MC3T3-E1 cells, TOPH-200 significantly attenuated intracellular reactive oxygen species and improved mitochondrial membrane potential. Importantly, TOPH-200 effectively enhanced osteogenic cell proliferation, differentiation, and mineralization in H2O2-treated MC3T3-E1 cells. Additionally, two novel peptides, DSQLAPFRF and HFNPRL, were screened from the TOPH-200 using PeptideRanker and molecular docking. Further cell experiments indicated that both peptides exhibited potent antioxidant and antiosteoporotic activities in oxidatively damaged MC3T3-E1 cells. In summary, mild ultrasound-assisted enzymatic hydrolysis proved effective in producing bioactive peptides from oysters, and these newly identified peptides exhibit potential for osteoporosis prevention.